1989
DOI: 10.1192/s0007125000291599
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Negative Symptoms

Abstract: When Kraepelin originally defined and described dementia praecox, he assumed that it was due to some type of neural mechanism. He hypothesised that abnormalities could occur in a variety of brain regions, including the prefrontal, auditory, and language regions of the cortex. Many members of his department, including Alzheimer and Nissl, were actively involved in the search for the neuropathological lesions that would characterise schizophrenia. Although Kraepelin did not use the term ‘negative symptoms', he d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1991
1991
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…Perhaps the acute onset of these symptoms is an energy-demanding state reflected in activation in brain imaging studies, whereas chronic symptoms relate to relative decrements in blood flow and glucose utilization. Support for this hypothesis comes from investigations in schizophrenic patients which have demonstrated that prefrontal activation is associated with the acute onset of specific psychotic symptoms (39,43) and from studies indicating that chronic symptoms, such as negative symptoms, are related to prefrontal hypofunction (40,44,45).…”
Section: Discussionmentioning
confidence: 96%
“…Perhaps the acute onset of these symptoms is an energy-demanding state reflected in activation in brain imaging studies, whereas chronic symptoms relate to relative decrements in blood flow and glucose utilization. Support for this hypothesis comes from investigations in schizophrenic patients which have demonstrated that prefrontal activation is associated with the acute onset of specific psychotic symptoms (39,43) and from studies indicating that chronic symptoms, such as negative symptoms, are related to prefrontal hypofunction (40,44,45).…”
Section: Discussionmentioning
confidence: 96%
“…The biological hypothesis has been canvassed by several other authors (1 1, 28, 62, 63), and it has been suggested that women with schizophrenia are more likely to have a familial form and less likely to have suffered a brain insult at birth (1 1,64). Crow's negative syndrome hypothesis (18) was based on the assumption that negative symptoms were caused by a cumulative neuronal loss, but this original formulation has required modification in the light of subsequent research (65), not least because deficit symptoms appear to occur before and not after the first episode (66).…”
Section: Gender Differences In Schizophreniamentioning
confidence: 99%
“…Frontal cortex dysfunction has been widely suggested to underlie 'negative' or 'deficit' symptoms of schizophre nia [1][2][3], and several lines of evidence have demon strated correlations of negative symptoms with frontal cortical abnormalities in schizophrenic patients. Recent studies using single-photon emission computed tomogra phy and positron emission tomography have supported a correlation between severity of negative symptoms and decreased activation of the frontal region with different cognitive tasks for frontal cortex activation [4][5][6][7], Various studies using measurement of regional cerebral blood flow (rCBF) with xenon-133 have shown decreased frontal flow in schizophrenic patients compared to normal con trols [5], but none of these studies have investigated the relation of this hypofrontality to negative symptoms.…”
Section: Introductionmentioning
confidence: 99%